2011
DOI: 10.1007/s11284-011-0842-3
|View full text |Cite
|
Sign up to set email alerts
|

Exotic thistles increase native ant abundance through the maintenance of enhanced aphid populations

Abstract: Exotic species change the structure and composition of invaded communities in multiple ways, but the sign of their impact on native species is still controversial. We evaluated the effects of the thistles Carduus thoermeri and Onopordum acanthium-two of the most abundant exotic plant species in disturbed areas of the Patagonian steppe-on the native tending ant assemblage. Exotic thistles showed an increased number of plants with aphids and had greater aphid density than native plants. Since native tending ants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Comparison to other published results is difficult owing to the still small number of studies on the effects of invasive plants on ant communities and the equivocality of their results. It seems that the invasive plants producing food which is used by ants, such as nutritious seeds, for example, or plants that enhance aphid populations may favour native ant populations (Alba-Lynn and Henk 2010; Lescano and Farji-Brener 2011). However, this is not always the case, as it was demonstrated by French and Major (2001), who showed that the exotic plant Acacia saligna, which produces ant-dispersed seeds, did not affect the species richness of ants and negatively affected their abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison to other published results is difficult owing to the still small number of studies on the effects of invasive plants on ant communities and the equivocality of their results. It seems that the invasive plants producing food which is used by ants, such as nutritious seeds, for example, or plants that enhance aphid populations may favour native ant populations (Alba-Lynn and Henk 2010; Lescano and Farji-Brener 2011). However, this is not always the case, as it was demonstrated by French and Major (2001), who showed that the exotic plant Acacia saligna, which produces ant-dispersed seeds, did not affect the species richness of ants and negatively affected their abundance.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, abundance of ants increases in invaded areas relative to native sagebrush (Ostoja et al 2009), which may result from increases in seeds or reduced seed predation by rodents in invaded areas (Anderson & MacMahon 2001). In the Patagonia steppe, activity of tending ants increases with invasive thistles due to a concomitant increase in aphids (Lescano & Farji-Brener 2011). Because ants represent diverse functional groups and are relatively easy to identify, research on this group can provide important insights.…”
Section: Effects On Antsmentioning
confidence: 99%
“…Consequently many of the exotic species that are expanding along disturbed areas, as well as many of the native species, may be subjected to herbivory by this ant. Also, several exotic and native species share the same aphid species, which are very common in the study site (Farji-Brener et al 2009;Lescano and Farji-Brener 2010). Other studies have also reported the attack of introduced plants by generalist aphids (Memmott et al 2000).…”
Section: Discussionmentioning
confidence: 85%